A Retrospective Patient Chart Review and Survey in Patients with Cryopyrin-associated Periodic Syndromes Treated with Anakinra - Helen J. Lachmann; Renée J.G. Arnold; Marco Gattorno; Isabelle Koné-Paut; Alberto Ferreira; Jasmin Kümmerle-Deschner (Journal of Health Economics and Outcomes Research)
**Background:** Cryopyrin-associated periodic syndromes (CAPS) is a group of rare autoinflammatory diseases. Little is known about the burden of disease, patients’ views on treatment, and adverse events (AEs) with current therapy.